Quantitative pulsed CEST-MRI using Ω-plots - Meißner, Jan-Eric; Görke, Steffen; Rerich, Eugenia; Klika, Karel D.; Radbruch, Alexander; Ladd, Mark E.; Bachert, Peter; Zaiss, Moritz (NMR in biomedicine, 2015)
Chemical exchange saturation transfer (CEST) allows the indirect detection of dilute metabolites in living tissue via MRI of the tissue water signal. Selective radio frequency (RF) with amplitude B1 is used to saturate the magnetization of protons of exchanging groups, which transfer the saturation to the abundant water pool. In a clinical setup, the saturation scheme is limited to a series of short pulses to follow regulation of the specific absorption rate (SAR). Pulsed saturation is difficult to describe theoretically, thus rendering quantitative CEST a challenging task. In this study, we propose a new analytical treatment of pulsed CEST by extending a former interleaved saturation-relaxation approach. Analytical integration of the continuous wave (cw) eigenvalue as a function of the RF pulse shape leads to a formula for pulsed CEST that has the same structure as that for cw CEST, but incorporates two form factors that are determined by the pulse shape. This enables analytical Z-spectrum calculations and permits deeper insight into pulsed CEST. Furthermore, it extends Dixon's Ω-plot method to the case of pulsed saturation, yielding separately, and independently, the exchange rate and the relative proton concentration. Consequently, knowledge of the form factors allows a direct comparison of the effect of the strength and B1 dispersion of pulsed CEST experiments with the ideal case of cw saturation. The extended pulsed CEST quantification approach was verified using creatine phantoms measured on a 7 T whole-body MR tomograph, and its range of validity was assessed by simulations. Copyright © 2015 John Wiley & Sons, Ltd.
Gesehen am 12.06.2020